Bamboo particleboards: recent developments - Gauss, Christian; De Araujo, Victor; Gava, Maristela [UNESP]; Cortez-Baibosa, Juliana [UNESP]; Savastano Junior, Holmer (Univ Federal Goias, 2019)
Due to the high dimensional variation of bamboo, the manufacturing of materials such as plywood and laminated bamboo produces a high amount of residues. The production of particleboards could be used to overcome this problem and become a viable solution to reuse the generated waste as a raw material to high value-added products. This study aimed to present an overview of the bamboo particleboard production, as well as the mechanical and physical properties of this material, followed by a review of the advances in its research and development. In general, independently of the resin or bamboo species utilization, several bamboo particleboards meet the mechanical properties requirements of international standards for wood-based medium-density particleboards. The main focus of this study is to provide a review, in order to support research groups interested in using new bamboo-based materials for the development of manufactured durable products.
Keywords: Bamboo panels; bamboo-based materials; lignocellulosic materials